Modeling hydrologic response due to the impact of land use changes in the Upper Bernam River basin using machine learning - Al-Heattar, Najeeb Mohammed Nagee (2019)
Land use changes in a watershed can affect the watershed hydrology in various ways. Some types of land development can be associated with increased impervious area causing an increase in surface runoff and a decrease in groundwater recharge. Both of these processes can have large-scale ramifications through time. Increased runoff results in higher flows during rainfall events, which in turn increases the number of times that a river floods the adjacent land areas. On the other hand, the groundwater recharge decreased due to the increase in the impervious surfaces and decrease in the soil infiltration rate.